2015
DOI: 10.1007/s10705-015-9719-0
|View full text |Cite
|
Sign up to set email alerts
|

Successional and seasonal variation in litterfall and associated nutrient transfer in semi-evergreen tropical forests of SE Mexico

Abstract: Forest conversion to agriculture and grassland has been widespread in south-eastern Mexico. The productivity, functioning and carbon dynamics of secondary forests growing after abandonment of agricultural fields are expected to differ from those of primary forests. This study analysed whether forest age and seasonal variations affect the amount and temporal distribution of litterfall and associated nutrient transfer. Litterfall was measured across a chronosequence of semi-evergreen tropical forest in Calakmul,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
29
1
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 55 publications
9
29
1
4
Order By: Relevance
“…Greater depositions tend to occur in forests at advanced stages of development (Pinto et al, 2008;Calvi et al, 2009;Menezes et al, 2010). In some cases, greater deposition was observed in advanced secondary forests compared with mature forests (Aryal et al, 2015). Still for areas of secondary Atlantic Forest, values higher than those found in this study were reported by Abreu et al (2010) ).…”
Section: Resultscontrasting
confidence: 44%
“…Greater depositions tend to occur in forests at advanced stages of development (Pinto et al, 2008;Calvi et al, 2009;Menezes et al, 2010). In some cases, greater deposition was observed in advanced secondary forests compared with mature forests (Aryal et al, 2015). Still for areas of secondary Atlantic Forest, values higher than those found in this study were reported by Abreu et al (2010) ).…”
Section: Resultscontrasting
confidence: 44%
“…Few studies investigated differences in litterfall seasonality among successional stages in tropical forest (Lawrence 2005;Kalácska et al 2005;Chave et al 2009;Aryal et al 2015). In TDFs of Southern Mexico, Lawrence (2005) observed that seasonal variations in litter production were more pronounced in old secondary and mature forests.…”
Section: Introductionmentioning
confidence: 99%
“…Although changes in aboveground biomass are the primary driver of biogeochemical processes in secondary tropical forests (Powers & Marín‐Spiotta, ), the rates of recovery of litter dynamics vary broadly across forest types. In secondary forests, litterfall rates have been found to return to, or even exceed, levels in primary forest within the first few decades (Ewel, ; Brown & Lugo, ; Barlow, Gardner, Ferreira, & Peres, ; Aryal, Jong, Ochoa‐Gaona, Mendoza‐Vega, & Esparza‐Olguin, ). Litter chemistry is also expected to change during forest succession due to differences in tree species composition, leaf longevity, nutrient acquisition, nutrient resorption, and defense strategy (Coley, ; Santiago & Wright, ; Cornwell et al, ; Wood, Lawrence, & Wells, ) although the evidence suggests few consistent trends (e.g., Dantas & Phillipson, ; Martius, Höfer, Garcia, Römbke, & Hanagarth, ; Huang et al, ).…”
Section: Introductionmentioning
confidence: 99%